The living wage: understanding the importance and impact / Nor Azira Ismail, Jamilah Laidin and Shahiszan Ismail - Ismail, Nor Azira; Laidin, Jamilah; Ismail, Shahiszan (Universiti Teknologi MARA, Kedah, 2023)
Over the past three years, the pandemic has severely impacted Malaysians from various income groups. Research conducted by the Department of Statistics Malaysia (2021) reveals that many households in the M40 category (middle-income group) have shifted to the B40 category (lowerincome group), comprising 20% of the total M40 households. Similarly, within the T20 group (highincome group), 12.8% have transitioned to the B40 category. This situation can be attributed to the rising cost of living due to increasing food prices, property and housing, education fees, and health services, which has particularly adversely affected the middle-income group. Other than that, the increase in living expenses has outpaced the minimum wage rate of RM1,500 per month received by employees. Unfortunately, this new minimum wage order falls significantly short of the average monthly household expenditure reported by the Department of Statistics Malaysia in 2022, amounting to RM5,150, which increased by 3.7% per year from 2019 until 2022. The justification for introducing a living wage stems from the ongoing rise in the cost of living. This rise in living costs is not aligned with the increase in wage rates that employees are receiving. Therefore, the topic of a living wage has become a contentious issue, as the relentless rise in the cost of living exhibits no signs of abating.